Andrej Dynko. (Another Sky: Writings from Prison Around the World, 2007)
The article focuses on the arrest of Adrej Dynko, the vice-editor-in-chief of the independent newspaper "Nasha Viva" and editor of the cultural magazine "Arche" in Minsk, Belarus. On March 21, 2006, he was arrested while on his way to October Square, reportedly to provide food and support to demonstrators who protest the national elections. He was sentenced of a ten-day imprisonment on charge of hooliganism and was released on April 1, 2006.